Transforming health professionals into population health change agents - Lucio Naccarella; Iain Butterworth; Timothy Moore (SAGE Publishing, 2016)
Background. With the recognition that professional education has not kept pace with the challenges facing the health and human service system, there has been a move to transformative education and learning professional development designed to expand the number of enlightened and empowered change agents with the competence to implement changes at an individual, organisation and systems level. Design and Methods. Since 2010, the Department of Health and Human Services in Victoria, Australia, in collaboration with The University of Melbourne's School of Population and Global Health, has delivered seven population health short courses aimed to catalyse participants' transformation into population health change agents. This paper presents key learnings from a combination of evaluation data from six population health short courses using a transformative learning framework from a 2010 independent international commission for health professionals that was designed to support the goals of transformative and interdependent health professionals. Participatory realist evaluation approaches and qualitative methods were used. Results. Evaluation findings reveal that there were mixed outcomes in facilitating participants' implementation of population health approaches, and their transformation into population health agents upon their return to their workplaces. Core enablers, barriers and requirements, at individual, organisational and system levels influence the capability of participants to implement population health approaches. The iterative and systemic evolution of the population health short courses, from a one off event to a program of inter-dependent modules, demonstrates sustained commitment by the short course developers and organisers to the promotion of transformative population health learning outcomes. Conclusions: To leverage this commitment, recognising that professional development is not an event but part of an ongoing transformative process, suggestions to further align recognition of population health professional development programs are presented.